Characterization of the co-chaperones of Hsp70 and Hsp90 in Trypanosoma brucei and their potential partnerships - Mokoena, Fortunate (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
African Trypanosomiasis, which is caused by Trypanosoma brucei, is one of the crippling agents of social and economic development in Africa. T. brucei cycles between the cold-blooded insect vector, the tsetse fly (Glossina spp), and warm-blooded mammalian hosts. T. brucei, T. cruzi and L. major are mammal infecting kinetoplastid parasites that are collectively referred to as TriTryps. These parasites experience extreme environments as they move between their warm-blooded mammalian hosts and cold-blooded insect vectors which trigger extensive morphological transformations during the life-cycle of the parasite. Molecular chaperones have been implicated in parasite differentiation. TriTryps display significant expansions and diversity in the gene complements encoding molecular chaperones, especially J-proteins. Generally, J-proteins function as co-chaperones of Hsp70s, forming part of vital protein homeostasis processes. Hsp70s show a high degree of conservation, while J-proteins appear to be an extreme case of taxonomic radiation. Although several studies have focused on the molecular and cell biology of Hsp70s in some kinetoplastid parasites, knowledge is still lacking pertaining to J-proteins and their partnerships with Hsp70s. This thesis focused on the classification of kinetoplastid Jproteins into the four types by examining the domain organizations using T. brucei as a guide. The potential partnership of J-proteins and Hsp70s were postulated based on predicted subcellular localization. Kinetoplastid parasites, particularly T. brucei, have evolved an expanded and specialized J-protein machinery, likely to be a consequence of an evolutionary fitness/trait to adapt to diverse environment present in hosts and vectors. These analyses will yield insight into the process of parasite differentiation as well as provide new leads for chemotherapeutic treatments. The presence of the STI1 mediated Hsp90 hetero-complex formation has not been confirmed in T. brucei. To this end, in silico and biochemical techniques were used to characterize the role of TbSTI1, as an adaptor protein of Hsp70 and Hsp90. Through domain architecture analysis, sequence alignments, phylogenetic analysis and three-dimensional structure prediction, TbSTI1 was demonstrated to be the most conserved TPR containing co-chaperone of Hsp70 and Hsp83 in T. brucei and also shown to be highly similar to its eukaryotic homologues. Recombinant TbSTI1 was overproduced and purified in E.coli cells and subsequently shown to associate with TcHsp70 in a concentration dependent manner and associate weakly with TbHsp70.4. TbSTI1 and TbHsp83 were also demonstrated to be expressed and upregulated upon exposure to heat shock at the bloodstream stage of parasite development. In conclusion, this study is the first to report the interaction of TbSTI1 with a chaperone. Interactions between TbSTI1 and Hsp70s were demonstrated and therefore, the formation of the hetero-complex is predicted based the similarity of TbSTI1 to other STI1 proteins.
Keywords: Uncatalogued